A Comparative Study of Immediate Annuities and Ordinary Annuities in establishing the Phantom of Zero Liability Under the Trusteeship Pension Valuation Structure - Michael, Ogungbenle Gbenga; Oluseyi, Adeoye Vincent (Journal of Business and Management, 2023)
Background: The liabilities of a pension scheme define the financial value to be paid at a definite period in the future. The underlying goal of pension plans is to provide retirees with sufficient stream of income to enable them to live a decent financially independent life post-employment period. The regulatory framework for occupational pension schemes necessitates the services of trustees as administrators who assume legal administrative responsibilities on the scheme and saddled to oversee actuarial valuations of the scheme's liabilities at definite points in time. Objectives: The objective of this paper is (i) to empirically examine the drivers of pension liability and how they are evaluated by the trustee’s model. (ii) Specifically, the study intends to use input parameters of the trustee model to establish the conditions for which the value of liability is zero under trusteeship annuity factor. Methods: This study applies trustees’ valuation model, the present values together with infinitesimal calculus. Salary data as well as demographic data were obtained from an agricultural production services company located in Jos-South, Nigeria. Results: Computational evidence from our results proves that the total service liability under the conditions of the current model is vanishingly zero. However, when the annuity factor is replaced by life table annuity, the service liability does not vanish. Conclusion: The total service liability obtained as zero therefore initiates inquiry as to whether this current valuation framework causes potential uncertainties for the pension trustees who are responsibly saddled with both administration and core decision-making responsibilities of the system.